PENINGKATAN HASIL BELAJAR BAHASA INDONESIA POKOK BAHASAN MENULIS OPINI DALAM ARTIKEL DENGAN MEDIA INFOGRAFIS PADA SISWA KELAS XII IPA 2 MAN IC PASER TAHUN PELAJARAN 2021-2022 - Susmini Susmini (Cross-border, 2021)
Student learning outcomes in XII IPA 2 class for the 2021-2022 learning year for the competence to write opinions in articles are still low.Students have difficulty in developing their ideas. This is caused by many factors, including the use of media and learning activities that are less varied, causing students' interest and enthusiasm in learning to be less and the results achieved are not optimal. With media in the form ofinfographicswill make it easier for students to express their ideas, when compared without the mediain the form of infographics.Therefore, the purpose of this research is to improve the skills of writing opinions in the articles of XII IPA 2 class of MAN Insan Cendekia Paser students by using infographic media.Infographic media is one of the media used in learning to write opinions in articles. This infographic media can stimulate students in expressing ideas creatively in writing opinions. The type of research used is Classroom Action Research (CAR). The subjects of this study were students of XII IPA 2 class of MAN Insan Cendekia Paser, as many as 24 students with details of 9 male students and 15 female students.The results showed that the ability to write opinions in articles based on infographics media can improve the opinion writing skills of XII class students of MAN Insan Cendekia in the 2021-2022 academic year.